Black colon. Issue 4 (13th March 2021) - Ahmed, Moiz; Sheth, Nirali; Bansal, Raghav
Key Clinical Message: Early diagnostic endoscopic evaluation is useful in evaluation of mucosal viability and possible endoscopic reduction in patients with sigmoid volvulus. Black‐brown mucosa is consistent with gangrene, a life‐threatening complication requiring surgery. Abstract : Early diagnostic endoscopic evaluation is useful in evaluation of mucosal viability and possible endoscopic reduction in patients with sigmoid volvulus. Black‐brown mucosa is consistent with gangrene, a life‐threatening complication requiring surgery.